2004
DOI: 10.1177/009318530403200402
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Reporting Child Abuse: Legal and Psychological Perspectives: Part Two: Emotional Abuse and Secondary Abuse

Abstract: Emotional abuse and secondary abuse of children are increasingly recognized within the mental health and legal professions as at least as damaging to adjustment as physical abuse, sexual abuse, and neglect. However, emotional and secondary abuse are relatively more difficult for mandated reporters to recognize and document, and reporting laws are problematic. This review article was written to acquaint professionals with the seriousness and prevalence of emotional and secondary child abuse and with the issues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The present study evaluated disclosure in relation to parental-figure emotional abuse, which has been viewed at times in the past as less damaging than other forms of childhood maltreatment (e.g., sexual and physical abuse) (Twaite & Rodriguez-Srednicki, 2004). In fact, earlier versions of the Diagnostic Statistics Manual criteria for post-traumatic stress disorder failed to include as a traumatic event exposure to emotional abuse incidents that did not involve injury or physical threat (American Psychiatric Association, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The present study evaluated disclosure in relation to parental-figure emotional abuse, which has been viewed at times in the past as less damaging than other forms of childhood maltreatment (e.g., sexual and physical abuse) (Twaite & Rodriguez-Srednicki, 2004). In fact, earlier versions of the Diagnostic Statistics Manual criteria for post-traumatic stress disorder failed to include as a traumatic event exposure to emotional abuse incidents that did not involve injury or physical threat (American Psychiatric Association, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The comparatively covert nature of PM can thus lead investigators to focus on other more “tangible” forms of maltreatment, as well as to adopt an apathetic or helpless outlook regarding how best to intervene. Perhaps of greatest concern (and of greatest relevance to the theme of this special section), laypersons, professionals, and larger systems may be induced to deny that PM constitutes a distinct form of abuse that carries its own potentially unique risks and consequences, and thus discount PM or misattribute its pernicious effects to other factors (Chamberland et al, 2005; Twaite & Rodriguez-Srednicki, 2004). The inherent subtlety and lack of recognition of PM as a pernicious form of abuse, per se, may thus contribute to its infrequent selection by practitioners as a primary focus of child-trauma intervention, or to the fact that few interventions exist that explicitly target PM (NCTSN, 2011).…”
mentioning
confidence: 99%
“…Numerous studies have demonstrated significant differences between children broadly classified as physically abused, sexually abused, neglected, and emotionally abused when using either legal definitions or the principle reason for a report in order to determine categorization, a common approach in differentiated maltreatment research (Zuravin, 1999). In addition to the cognitive, academic, and other deficits generally present across undifferentiated groups of maltreated children, reviews of studies in which children are divided by maltreatment type have consistently revealed physically abused children to be comparably more aggressive and violent than other maltreated groups, sexually abused children to be more anxious and depressed, neglected children to be more socially unskilled, and psychologically abused children to be more emotionally blunted and guarded (Rodriguez-Srednicki & Twaite, 2004; Trickett & McBride-Chang, 1995; Twaite & Rodriguez-Srednicki, 2004; Veltman & Browne, 2001). Therefore, it is reasonable to suspect there may be differences in various domains of adaptive functioning between children who have experienced different types of maltreatment.…”
mentioning
confidence: 99%